LINGUISTIC NATURE AND THEORETICAL FOUNDATIONS OF THE CATEGORY OF AMBIVALENCE - Pardayeva Dilora Ilyos qizi (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the linguistic nature of the category of ambivalence, its semantic-pragmatic characteristics, and its theoretical interpretations in contemporary linguistics. Ambivalence is explored as a complex phenomenon that reflects the simultaneous manifestation of contradictory semantic, emotional, and evaluative attitudes within human cognition and communicative activity. The study provides a scientific analysis of the mechanisms through which ambivalence is realized in linguistic units, with particular emphasis on its functional potential in literary texts and discourse. Furthermore, the category is investigated in relation to modality, expressiveness, evaluation, and pragmatic layers of meaning. The article analyzes the theoretical contributions of structural-semantic, pragmalinguistic, and discourse-oriented approaches to understanding the linguistic essence of ambivalence and substantiates its significance as one of the important conceptual categories in modern linguistic research.